Insulin Reduces Inflammation by Regulating the Activation of the NLRP3 Inflammasome - Chang, Yu-Wei; Hung, Ling-Chien; Chen, Yu-Cheng; Wang, Wen-Hung; Lin, Chun-Yu; Tzeng, Hsin-Han; Suen, Jau-Ling; Chen, Yen-Hsu (Frontiers in Immunology, 2021)
The NOD-, LRR-, and pyrin domain-containing protein 3 (NLRP3) inflammasome is the platform for IL-1β maturation, aimed at mediating a rapid immune response against danger signals which must be tightly regulated. Insulin is well known as the critical hormone in the maintenance of glucose in physiologic response. Previous studies have proved insulin has the anti-inflammation effect but the molecular mechanism of immunomodulation provided by insulin is not clear so far. Here we investigated whether insulin reduces inflammation by regulating the NLRP3 inflammasome. In the present study, we used LPS and ATP to induce the intracellular formation of the NLRP3 inflammasome. Insulin inhibited the secretion of IL-1β by preventing the assembly of the ASC in THP-1 cells and human CD14+ monocyte-derived macrophages. The phosphorylation status of Syk, p38 MAPK, and ASC were altered by insulin. These effects were attenuated in THP-1 cells transfected with small interfering RNA targeting insulin receptors. In vivo, administration of glucose–insulin–potassium reduced serum IL-1β level, intestinal ASC speck formation, local macrophage infiltration, and alleviated intestinal injury in mice exposed to LPS. Insulin may play an immunomodulatory role in anti-inflammation by regulating the NLRP3 inflammasome.